Health‐related quality of life of patients with colorectal neoplasms in China: A multicenter cross‐sectional survey. Issue 5 (22nd September 2020) - Huang, Hui‐Yao; Wang, Hong; Shi, Ju‐Fang; Bai, Ya‐Na; Wang, Le; Liu, Cheng‐Cheng; Yan, Xin‐Xin; Liu, Guo‐Xiang; Liao, Xian‐Zhen; Shi, Dian; Mao, A‐Yan; Ren, Jian‐Song; et al.
Abstract: Background and Aim: This study aimed to clarify health‐related quality of life (HRQoL) of patients with colorectal precancer and colorectal cancer (CRC) in China and to better understand related utility scores. Methods: A hospital‐based cross‐sectional survey was conducted in precancer and CRC patients from 2012 to 2014, covering 12 provinces in China. HRQoL was assessed with EuroQol 5‐Dimensions 3‐Levels. Utility scores were derived using Chinese value set. A multivariate regression model was established to explore potential predictors of utility scores. Results: A total of 376 precancer (mean age 58.7 years, 61.2% men) and 2470 CRC patients (mean age 58.6 years, 57.6% men) were included. In five dimensions, there was a certain percentage of problem reported among precancer (range: 12.0% to 36.7%) and CRC (range: 32.4% to 50.3%) patients, with pain/discomfort being the most serious dimension. Utility scores of precancer and CRC patients were 0.870 (95% confidence interval [CI], 0.855–0.886) and 0.751 (95% CI, 0.742–0.759), both of which were lower than those of general Chinese population (0.960 [95% CI, 0.960–0.960]). Utilities for patients at stage I to stage IV were 0.742 (95% CI, 0.715–0.769), 0.722 (95% CI, 0.705–0.740), 0.756 (95% CI, 0.741–0.772), and 0.745 (95% CI, 0.742–0.767), respectively. Multivariate analysis showed that therapeutic regimen, time point of the interview, education, occupation, annual household income, and geographic region were associated with utilities of CRC patients. Conclusion: Health‐related quality of life of both precancer and CRC patients in China declined considerably. Utility scores differed by sociodemographic and clinical characteristics, and findings of these utilities may facilitate implementation of further cost–utility evaluations.